2013
DOI: 10.1084/jem.20130240
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human CCR8 as a CCL18 receptor

Abstract: CCL18 is an endogenous agonist of the human CCR8 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 31 publications
6
161
2
1
Order By: Relevance
“…The recent identification of CCR8 as the major receptor of CCL18 has permitted the functional evaluation of CCL18 and its murine analog CCL8. 13 In our study, immunohistochemical analysis revealed the presence of CCL18 in intrarenal cells with a mononuclear appearance. Consecutive sections identified macrophages and myeloid DCs 25 coexpressing CCL18.…”
Section: Adoptively Transferred Monocytes Restore Kidney Injury In Nesupporting
confidence: 58%
See 2 more Smart Citations
“…The recent identification of CCR8 as the major receptor of CCL18 has permitted the functional evaluation of CCL18 and its murine analog CCL8. 13 In our study, immunohistochemical analysis revealed the presence of CCL18 in intrarenal cells with a mononuclear appearance. Consecutive sections identified macrophages and myeloid DCs 25 coexpressing CCL18.…”
Section: Adoptively Transferred Monocytes Restore Kidney Injury In Nesupporting
confidence: 58%
“…In 2013, Islam et al 13 reported the murine CCL8 (mCCL8) as its functional analog. Both chemokines acted through CC chemokine receptor 8 (CCR8) and were induced in alternatively activated macrophages [14][15][16][17] as well as in similar diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CCR8 is a beta chemokine receptor with a known role in induction of chemotaxis in Th2 cells via its two ligands CCL1 and CCL18 [50], and functions as a co-receptor for enveloped viruses including HIV [51,52]. The CCR8 axis has been found to be activated in urothelial and renal carcinomas resulting in immune response impairment, and it is responsible for apoptosis inhibition in lymphoma [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to fibrosis, CCL18 has been found to be elevated in EoE [47]. Studies by the Luster laboratory identified CCR8 as the CCL18 receptor, and both were found to be elevated in active EoE biopsies [48]. Together, these studies have translational implications for both anti-eosinophil strategies using biologics that provide siglec-8, IL-13, CCR8, and/or mast cell blockade.…”
Section: New Pathophysioloigic Insights Have Potential Therapeutic Valuementioning
confidence: 87%